2009
DOI: 10.3892/or_00000602
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of single isolated glands in gastric cancers and their surrounding gastric intestinal metaplastic mucosa

Abstract: Abstract. The biological properties and underlying genetics of gastric cancer and gastric intestinal metaplasia evolve with neoplastic progression from the genetics of the original gland cell. PCR assay with crypt isolation was used in tumors from 20 patients to examine microsatellite alterations (allelic imbalance at 17p, 5q, 18q, 3p, 4p, and 9p, and microsatellite instability) in glands from each tumor and from intestinal metaplastic lesions. Tumor specimens were processed as either pooled-gland samples or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…found that the incidence of genetic instability [including microsatellite instability (MSI) and loss of heterozygosity (LOH)] was 48% in IM with concurrent gastric cancer and 21% in IM with gastritis only . More recent studies of randomly dissected IM glands suggest that localized alteration in the MSs might have occurred, even though they were undetectable with bulk samples …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…found that the incidence of genetic instability [including microsatellite instability (MSI) and loss of heterozygosity (LOH)] was 48% in IM with concurrent gastric cancer and 21% in IM with gastritis only . More recent studies of randomly dissected IM glands suggest that localized alteration in the MSs might have occurred, even though they were undetectable with bulk samples …”
mentioning
confidence: 99%
“…11 More recent studies of randomly dissected IM glands suggest that localized alteration in the MSs might have occurred, even though they were undetectable with bulk samples. 12 Since the acquisition of the ability to generate genomic mutations or tolerate accelerated genomic changes is a critical step in the development of malignancy, 13 highly localized and stochastic genomic alterations would have provided an important annotation for the importance of the IM tissues in the cascade toward malignancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PCR-allelic imbalance (AI) analyses were performed using a thermal cycler (GeneAmp PCR System 9600; Perkin-Elmer, CA, United States) according to previously reported procedures[3]. AIs on chromosomes 1p, 3p, 4p, 5q, 8p, 9p, 13q, 17p, 18p, and 22q were examined using 22 highly pleomorphic microsatellite markers (D1S228, D1S548, D3S2402, D3S1234, D4S2639, D4S1601, D5S107, D5S346, D5S299, D5S82, D8S201, D8S513, D8S532, D9S171, D9S1118, D13S162, TP53, D18S487, D18S34, D22S274, D22S1140, and D22S1168).…”
Section: Case Reportmentioning
confidence: 99%
“…A recent study of IM tissues from the periphery of resected cancer tissues found that there was considerable genomic instability at this stage 5 6. However, since these tissues coinhabit the same microenvironment as cancer and presumably over a prolonged period time, it is critical to determine whether such pervasive genetic instability is an inherent and early property of IM tissue alone.…”
Section: Introductionmentioning
confidence: 99%